2004
DOI: 10.1614/wt-03-156r1
|View full text |Cite
|
Sign up to set email alerts
|

Sweet Corn Cultivar Sensitivity to Bentazon

Abstract: Five sweet corn cultivars were evaluated for tolerance to bentazon in five field experiments conducted during 2 yr in Ontario. Bentazon was applied postemergence (POST) at 1.08 and 2.16 kg ai/ha, the highest registered rate and twice the highest registered rate, respectively, used in sweet corn in Ontario. When bentazon was applied POST at 1.08 and 2.16 kg/ha to sweet corn cultivar ‘DelMonte 2038’, injury included plant stunting and leaf damage ranging from 6 to 69% and 15 to 90%, respectively. Plant height wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 12 publications
(17 reference statements)
3
24
0
Order By: Relevance
“…This fact can be attributed to the fast effect of this herbicide on the integrity of the membranes, leading to rapid and widespread leaf necrosis (Diebold et al 2004). This also explains the high values of phytotoxicity symptom even at half of the commercial dose applied ( Figure 2B).…”
Section: Herbicide Selectivity In Alfalfa Cropsmentioning
confidence: 99%
“…This fact can be attributed to the fast effect of this herbicide on the integrity of the membranes, leading to rapid and widespread leaf necrosis (Diebold et al 2004). This also explains the high values of phytotoxicity symptom even at half of the commercial dose applied ( Figure 2B).…”
Section: Herbicide Selectivity In Alfalfa Cropsmentioning
confidence: 99%
“…However, other herbicides such as bentazon [11], isoxaflutole [17], mesotrione [13], nicosulfuron [14,23], nicosulfuron plus rimsulfuron [24,25], primisulfuron [16], prosulfuron [12] or thifensulfuron-methyl [18] have been shown to cause significant injury in some sweet maize hybrids.…”
Section: Crop Injurymentioning
confidence: 99%
“…However, other studies have reported significant injury in some sweet maize hybrids with certain herbicides. Diebold et al (2003Diebold et al ( , 2004 [10] reported up to 94% reduction in yield with formsulfuron in sweet maize. Similar yield reduction were reported with mesotrione [13], nicosulfuron [14], foramsulfuron [10] and nicosulfuron plus rimsulfuron [24,25] in some sensitive sweet maize hybrids.…”
Section: Yieldmentioning
confidence: 99%
See 1 more Smart Citation
“…Laudis is a newly developed herbicide whose active ingredient is tembotrione, a member of the triketone class of herbicides (Santel, 2009 (Robinson et al, 1994), photosystem II (Diebold et al, 2004), and hydroxyphenyl pyruvate dioxygenase (HPPD). Acetolactate synthase from mutants of tobacco and cotton (Nicotiana tabacum, Gossypium hirsutum) for tolerance to a triazolopyrimidine sulfonanilide displayed different levels of insensitivity to feedback inhibitors valine and/or leucine (Subramanian et al, 1991).…”
Section: Introductionmentioning
confidence: 99%